GE_GERICHTE C/7017/2017 vom 2. August 2018 - GE Cour de justice (2018)
BAIL À LOYER ; QUALITÉ POUR AGIR ET RECOURIR ; DIMINUTION DE LOYER ; TAUX D'INTÉRÊT ; FRAIS D'EXPLOITATION | OBLF.201; CPC.151; OBLF.16; CO.269a.lete